Immunobiology of Natural Killer Cell Receptors - Vivier, Eric.; Vivier, Eric.; Colonna, Marco.; Colonna, Marco. (Current Topics in Microbiology and Immunology, 2006)
Natural Killer (NK) cells are large granular lymphocytes of the innate immune system. They are widespread throughout the body, being present in both lymphoid organs and non-lymphoid peripheral tissues. NK cells are involved in direct innate immune reactions against viruses, bacteria, parasites and other triggers of pathology, such as malignant transformation, all of which cause stress in affected cells. Importantly, NK cells also link the innate and adaptive immune responses, contributing to the initiation of adaptive immune responses and executing adaptive responses using the CD16 FcgRIIIA immunoglobulin Fc receptor. Such responses are mediated through two major effector functions, the direct cytolysis of target cells and the production of cytokines and chemokines. The authors focus here on the nature of recognition events by NK cells and address how these events are integrated to trigger these distinct and graded effector functions.